A model of emotion and computer abuse - Kim, J.; Baskerville, Richard; Park, E. (Elsevier, 2016)
Internal computer abuse has received considerable research attention as a significant source of IS security incidents in organizations. We examine the effects of both organizational and individual factors on individuals’ computer abuse intent. A theoretical model is developed based on two theories: abuse opportunity structure and emotion process. We empirically tested the model with 205 working professionals. We found that the abuse opportunity structure in organizations affects an individual’s goal conduciveness, which in turn affects their abuse-positive affect. We also found that morality affects the abuse-positive affect, which in turn mediates the relationship between morality and abuse intent.